The Use of Euphemisms in the Book of “The Alchemist” by Paulo Coelho - Smirna Br Tarigan; Marlin Steffi Marpaung (Universitas Pendidikan Mandalika, 2023)
Euphemisms are a linguistic phenomenon whereby milder or courteous words are substituted for blunt or unpleasant expressions. This study focuses on the use of euphemisms and related expressions in Paulo Coelho's book,